Tata Kelola Properti Panggung dalam Talkshow Bincang Senja sebagai Media Edukasi Seni bagi Remaja - Taufik Mawardi; Nahdlatuzzainiyah Nahdlatuzzainiyah (CV. Global Cendekia Inti, 2026)
The article on stage property management in the talk show “Tak Senja” as an art education medium for teenagers examines the form, function, and aesthetics of properties used across six live broadcast episodes. The study employs a pictorial analysis approach using visual data from video documentation shared through social media, with data sourced from complete recordings of the program. The findings reveal that all six episodes of Bincang Senja demonstrate increasing maturity in property design to support themes set by the program director. In episode 1.0, the property arrangement reflects a careful strategy to avoid creating a “shock effect” for audiences accustomed to formal and rigid art discussions, by not immediately presenting a fully relaxed set. Episode 2.0 introduces a more relaxed atmosphere. Episodes 3.0 and 4.0 simplify the visual setting compared to earlier episodes. In episode 5.0, the set features a white table and chairs complemented by a book as a supporting prop. Episode 6.0 adopts a warm cream color scheme, with a music box as the main property, creatively used as a seat by the host. Overall, the properties are designed to create a communicative and welcoming visual atmosphere while maintaining aesthetic value. The transition from semi-formal to casual settings reflects a gradual strategy in enhancing visual engagement. This study highlights the importance of effective property management in supporting the delivery of artistic and literary values in a contextual, appealing, and youth-oriented manner.